Public Export Guarantees and Foreign Trade Structure - Peter Egger; Thomas Url (Austrian Institute of Economic Research (WIFO), 2004)
Inter-industry trade and foreign trade are usually not based on cash transactions; rather sales on credit are the rule. The resulting monitoring costs for lenders and the risk of default on accounts receivable form an additional part of transaction costs in trade. Export credit certainly faces higher transaction costs due to differences in language, business practice, jurisdiction, and payment enforceability between trading partners. Export credit insurance has long been a domain of public export credit agencies, but since the beginning of the 1980's private insurance is gaining ground. Using disaggregated panel data for goods exports from Austria, we show that public export guarantees have a more than proportional positive impact on trade volumes. Export guarantees predominantly affect the country structure of foreign trade, but leave the industry specialization almost constant.
Keywords: F13; H8; C23; 330; trade credit; export credit insurance; foreign trade structure; panel regression; Exportkreditversicherung; Außenhandelsstruktur; Gravitationsmodell; Panel